2012
DOI: 10.1097/qai.0b013e31825b5e06
|View full text |Cite
|
Sign up to set email alerts
|

Time to Initiate Antiretroviral Therapy Between 4 Weeks and 12 Weeks of Tuberculosis Treatment in HIV-Infected Patients

Abstract: In middle-income countries where ART is initiated at CD4 count of <350 cells per cubic millimeter, immediate initiation of ART in HIV-infected patients with active TB was not associated with survival advantage when compared to initiation of ART at 12 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 20 publications
2
45
0
Order By: Relevance
“…Kumarasamy [25] [25] Pedral-Sampaio et al [35] Tansuphasawadikul et al [53] Naidoo et al in South Africa [59] and CARINEMO in Mozambique [58]), two in Asia, TIME in Thailand [53] and CAMELIA in Cambodia [20] and STRIDE [21] was conducted across four continents as described above. Four of the five RCTs (SAPiT, STRIDE, CAMELIA and TIME) investigated different strategies with respect to the timing of ART initiation among TB patients.…”
Section: • Study Characteristicsmentioning
confidence: 99%
“…Kumarasamy [25] [25] Pedral-Sampaio et al [35] Tansuphasawadikul et al [53] Naidoo et al in South Africa [59] and CARINEMO in Mozambique [58]), two in Asia, TIME in Thailand [53] and CAMELIA in Cambodia [20] and STRIDE [21] was conducted across four continents as described above. Four of the five RCTs (SAPiT, STRIDE, CAMELIA and TIME) investigated different strategies with respect to the timing of ART initiation among TB patients.…”
Section: • Study Characteristicsmentioning
confidence: 99%
“…Even a brief delay made a huge difference. Recent trial results in Thailand could not find any significant difference when comparing ART initiated in patients after four weeks compared with ART started in patients at 12 weeks [32]. However, a brief delay in starting ART 4 to 8 weeks after the initiation of TB therapy in patients with CD4 + T cell counts more than 200 cells/mm 3 did not convey any increase in the risk of a new AIDSdefining illness or death, with a reduced risk of IRIS [29].…”
Section: Timing Of Art and Tb Treatmentmentioning
confidence: 90%
“…In a subsequent article, in a smaller population, Mansuthi et al [19] reported no benefit in early initiation of ART in coinfected patients with a CD4 count of less than 350 cells/ml. Similarly Török et al [20 & ] showed no benefit in patients with HIV-associated TB meningitis although the study participants were severely immunosuppressed, median CD4 count less than 50 cells/ml.…”
Section: Anti-retroviral Therapy In Tuberculosis Patientsmentioning
confidence: 96%